Detoxification strategies of triptolide based on drug combinations and targeted delivery methods. (15th March 2022) - Cao, Zhiwen; Liu, Bin; Li, Li; Lu, Peipei; Yan, Lan; Lu, Cheng
Abstract: Tripterygium wilfordii Hook f. has a long history of use in Chinese medicine. Triptolide (TP), as its main pharmacological component, has been widely explored in various diseases, including systemic lupus erythematosus, rheumatoid arthritis and cancer. However, due to its poor water solubility, limited therapeutic range and multi-organ toxicity, TP's clinical application has been greatly hampered. To improve its clinical potential, many attenuated drug combinations have been developed based on its toxicity mechanism and targeted delivery systems aimed at its water-solubility and structure. This review, conducted a systematic review of TP detoxification strategies including drug combination detoxification strategies from metabolic and toxic mechanisms, as well as drug delivery detoxification strategies from the prodrug strategy and nanotechnology. Many detoxification strategies have demonstrated promising potential in vitro and in vivo due to previous extensive studies on TP. Therefore, summarizing and discussing TP detoxification strategies for clinical problems can serve as a reference for developing novel TP detoxification strategies, and provide opportunities for future clinical applications.